Acute Low-Intensity Aerobic Exercise Modulates Intracortical Inhibitory and Excitatory Circuits in an Exercised and a Non-exercised Muscle in the Primary Motor Cortex - Yamazaki, Yudai; Sato, Daisuke; Yamashiro, Koya; Nakano, Saki; Onishi, Hideaki; Maruyama, Atsuo (Frontiers in Physiology, 2019)
Recent studies have reported that acute aerobic exercise modulates intracortical excitability in the primary motor cortex (M1). However, whether acute low-intensity aerobic exercise can also modulate M1 intracortical excitability, particularly intracortical excitatory circuits, remains unclear. In addition, no previous studies have investigated the effect of acute aerobic exercise on short-latency afferent inhibition (SAI). The aim of this study was to investigate whether acute low-intensity aerobic exercise modulates intracortical circuits in the M1 hand and leg areas. Intracortical excitability of M1 (experiments 1 and 2) and spinal excitability (experiment 3) were measured before and after acute low-intensity aerobic exercise. In experiment 3, skin temperature was also measured throughout the experiment. Transcranial magnetic stimulation was applied over the M1 non-exercised hand and exercised leg areas in experiments 1 and 2, respectively. Participants performed 30 min of low-intensity pedaling exercise or rested while sitting on the ergometer. Short- and long-interval intracortical inhibition (SICI and LICI), and short-latency afferent inhibition (SAI) were measured to assess M1 inhibitory circuits. Intracortical facilitation (ICF) and short-interval intracortical facilitation (SICF) were measured to assess M1 excitatory circuits. We found that acute low-intensity aerobic exercise decreased SICI and SAI in the M1 hand and leg areas. After exercise, ICF in the M1 hand area was lower than in the control experiment, but was not significantly different to baseline. The single motor-evoked potential, resting motor threshold, LICI, SICF and spinal excitability did not change following exercise. In conclusion, acute low-intensity pedaling modulates M1 intracortical circuits of both exercised and non-exercised areas, without affecting corticospinal and spinal excitability.